Are Aquaporins Expressed in Stomatal Complexes Promising Targets to Enhance Stomatal Dynamics? - Ding, Lei; Chaumont, François (Frontiers in Plant Science, 2020)
The opening and closure of stomata depend on the turgor pressure adjustment by the influx or efflux of ions and water in guard cells. In this process, aquaporins may play important roles by facilitating the transport of water and other small molecules. In this perspective, we consider the potential roles of aquaporins in the membrane diffusion of different molecules (H2O, CO2 and H2O2), processes dependent on abscisic acid and CO2 signaling in guard cells. While the limited data already available emphasizes the roles of aquaporins in stomatal movement, we propose additional approaches to elucidate the specific roles of single or several aquaporin isoforms in the stomata and evaluate the perspectives aquaporins might offer to improve stomatal dynamics.